1993
DOI: 10.1063/1.354387
|View full text |Cite
|
Sign up to set email alerts
|

Phase transitions during solid-state formation of cobalt germanide by rapid thermal annealing

Abstract: Phase transitions that involve solid-state reactions between cobalt and thin films of germanium have been investigated. Germanides are formed by reacting Co (300 Å thick) with thin layers of Ge (∼2000 Å thick) deposited on silicon substrates. Germanium was deposited on Si by rapid thermal chemical-vapor deposition and cobalt was deposited onto Ge by evaporation. The Co/Ge/Si stacked structure samples were then rapid thermally annealed at atmospheric pressure in an inert ambient consisting of Ar. Using x-ray-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 12 publications
3
16
0
Order By: Relevance
“…[1][2][3][4][5] Although there is a considerable amount of literature on crystallography, microstructure, phase formation, and electronic properties of various cobalt silicides due to their potential as self-aligned silicides, there are relatively few publications concerning structure and properties of cobalt germanides. [1][2][3][4][5] Although there is a considerable amount of literature on crystallography, microstructure, phase formation, and electronic properties of various cobalt silicides due to their potential as self-aligned silicides, there are relatively few publications concerning structure and properties of cobalt germanides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] Although there is a considerable amount of literature on crystallography, microstructure, phase formation, and electronic properties of various cobalt silicides due to their potential as self-aligned silicides, there are relatively few publications concerning structure and properties of cobalt germanides. [1][2][3][4][5] Although there is a considerable amount of literature on crystallography, microstructure, phase formation, and electronic properties of various cobalt silicides due to their potential as self-aligned silicides, there are relatively few publications concerning structure and properties of cobalt germanides.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] In addition, because of the importance of contacts to Si 1−x Ge x alloys, some groups investigate the reaction of Co with Si 1−x Ge x , rather than Ge, layers, which adds complexity to the understanding of germanide formation kinetics. 5 Ashburn et al 1 found Co 5 Ge 7 and CoGe 2 in SPE of Co/Ge/Si(001) after a rapid thermal anneal (RTA) at 573 K and 698 K, respectively. 16 Co 2 Ge was found to form between Co and Ge layers after ion beam mixing by Dhar and Kulkarni.…”
Section: Introductionmentioning
confidence: 99%
“…Among these approaches, germanium carries additional benefits in higher dopant solid solubility, which can further reduce parasitic resistance, and lower thermal budget for dopant activation, which is promising for highdielectric integration. While traditional silicides cannot be formed when selective Ge is used, promising results on the formation of metal germanides have been obtained [41], [42], which could further reduce the series resistance.…”
Section: Ultrathin Body Single-gate Mosfetmentioning
confidence: 99%
“…The reactions of germanium with Pt [ 5 , 6 , 7 ], Ni [8,9,10,11,12], Pd [6,9,13,14,15] and Co [9,13,16,17] have also been investigated previously. Study of the solid state reaction between the metal films and germanium to determine the phase formation sequence [5,9,11,13,15,17], microstructure of material [9,10,12], growth kinetics [11,16] and electrical characteristics [9,10,12],were analyzed by x-ray diffraction, Rutherford backscattering spectroscopy, transmission electron microscopy, differential calorimetry and current-voltage (I-V) techniques respectively.…”
mentioning
confidence: 98%
“…Study of the solid state reaction between the metal films and germanium to determine the phase formation sequence [5,9,11,13,15,17], microstructure of material [9,10,12], growth kinetics [11,16] and electrical characteristics [9,10,12],were analyzed by x-ray diffraction, Rutherford backscattering spectroscopy, transmission electron microscopy, differential calorimetry and current-voltage (I-V) techniques respectively. Thanailakis et al [8] established a relationship between asdeposited Pd/n-Ge (111) and Ni/n-Ge (111) Schottky barrier height values, the metal work functions and the density of surface states of germanium substrate.…”
mentioning
confidence: 99%